Repair and remodeling of the mandibular head of the condylar process in four immature dogs - Sauvé, Christopher P.; Fiani, Nadine; Peralta, Santiago; Hatcher, David C.; Arzi, Boaz (Frontiers in Veterinary Science, 2023)
Spontaneous repair and remodeling of the mandibular head of the condylar process is a rarely reported outcome following condylectomy. This clinical report describes the spontaneous repair and subsequent remodeling of the mandibular head of the condylar process in four immature dogs that sustained traumatic injuries, necessitating surgical intervention through arthroplasty via partial or complete condylectomy, or caudal mandibulectomy. In subsequent evaluations, it was observed that all dogs exhibited clinically functional TMJs, as evidenced by an appropriate range of motion. These findings were corroborated by the owners' reports of the patient's normal eating and drinking abilities. Conventional and cone-beam computed tomography studies demonstrated the repair and remodeling of the osseous tissues of the mandibular head of the condylar process. Histopathology was unavailable to assess the novel tissues. No evidence of intraarticular or extraarticular ankylosis or osteoarthritic changes was observed. 1 Introduction The temporomandibular joint (TMJ) is a synovial joint composed of the mandibular head of the condylar process and the mandibular fossa of the squamous temporal bone (1,2). In the canine species, morphological and morphometric descriptions of the TMJ have identified substantial anatomical variations in the shape of both the mandibular head of the condylar process and the retroarticular process, as well as variations in the depth of the mandibular fossa and the congruity between the joint's bones (2,3). Furthermore, specific dog breeds may also show variations in the shape of the mandibular head of the condylar process and the condylar process within their breed (3).